Optimization of Balance and Flexibility Through the Rationalization of Methods in the Educational Process for Primary School Students (Ages 6-10) - BĂLOI (PUTA), Carla Silvia; PETRACOVSCHI, Simona; PUTA, Tiberiu Silviu (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2024)
Introduction: In physical education lessons, the proper rationalization of methods targeting psychomotor components will lead to improved coordination, perception, and analysis of body movements and the movements of its various parts in their interaction. A rationalized training system applied in teaching can prevent the phenomenon of insufficient or excessive exercise, promoting the standardized performance of exercises, which plays an important role in students’ physical and mental health. Objective: The general objective of this study is the rationalization of specific methods aimed at optimizing balance and flexibility in the instructional process for students aged 6-10 years. Methods: The Flamingo Test was used to determine lower body balance, and the Sit and Reach Test was used to measure flexibility. Results: The results of this study revealed significant differences in balance and flexibility performance among students in grades 1-4, both by gender and overall. The Mann-Whitney and Wilcoxon tests were used to evaluate these differences. For balance on one leg, p-values ranged from 0.003 to 0.75, indicating significant differences in some classes, particularly in grades 1 and 2. Flexibility, measured through jumping tests, showed significant differences in grade 2 (p=0.011) and grade 1 (p=0.032). These findings suggest the need for personalized interventions in balance and flexibility training to optimize physical development at these ages. Conclusions: Proper structuring of exercises, based on a detailed assessment of each student’s individual needs, facilitates improvements in balance and flexibility. This is reflected in both student performance and physical activities, having a positive impact on the overall educational process.